Postulates of oncology alertness for an outpatient therapist: let’s look at the example of lung cancer - A. L. Vertkin; M. A. Rudnitskaya; Yu. V. Vakhabova; G. Yu. Knorring (Лечащий Врач, 2024)
Background. Currently, in our country, as well as throughout the world, there is a steady increase in the incidence of cancer, which is explained by several reasons, including the aging of the population, environmental, economic and other factors. According to the Global Cancer Observatory, lung cancer is the most common cancer in the world, accounting for more than 12.4% of the total number of new cancer cases, and it is this variant of malignant tumors that is recognized as the main cause of death from cancer (1.8 million cases, 18.7% of the total number of deaths from cancer in 2022 worldwide). The solution to this serious medical and social problem is seen in increasing the effectiveness of detecting early stages of cancer at an early stage, including at the outpatient stage of medical care. The formation and maintenance of skills of oncological alertness among doctors of almost all specialties can ensure the detection and reduction of the frequency of detection of advanced/late-stage tumors, which means it will help to start specialized treatment earlier. The identification of complaints and symptoms characteristic of oncological diseases using algorithmized approaches and methodological support, followed by consultation of the patient with a pulmonologist or oncologist, are designed to improve the results of treatment.Results. The article suggests the rules of oncological alertness for their unconditional application at the outpatient stage by therapists and general practitioners, analyzing lung cancer as an example, considering a set of specially designed printed materials that facilitate the implementation of the principles of oncological alertness.